A 350‐million‐year legacy of fire adaptation among conifers. (29th December 2015) - He, Tianhua; Belcher, Claire M.; Lamont, Byron B.; Lim, Sim L.
Summary: Current phylogenetic evidence shows that fire began shaping the evolution of land plants 125 Ma, although the fossil charcoal record indicates that fire has a much longer history (>350 Ma). Serotiny (on‐plant seed storage) is generally accepted as an adaptation to fire among woody plants. We developed a conceptual model of the requirements for the evolution of serotiny, and propose that serotiny is only expressed in the presence of a woody rachis as supporting structure, compact scales covering seeds as protective structure, seed wing as dispersal structure, and crown fire as the agent of selection and mechanism for seed release. This model is strongly supported by empirical data for modern ecosystems. We reconstructed the evolutionary history of intrinsic structural states required for the expression of serotiny in conifers, and show that these were diagnostic for early ('transitional') conifers from 332 Ma (late‐Carboniferous). We assessed the likely flammable characteristics of early conifers and found that scale‐leaved conifers burn rapidly and with high intensity, supporting the idea that crown fire regimes may have dominated early conifer ecosystems. Synthesis . Coupled with strong evidence for frequent fire throughout the Permian‐Carboniferous and fossil evidence for other fire‐related traits, we conclude that many early conifers were serotinous in response to intense crown fires, indicating that fire may have had a major impact on the evolution of plant traits as far back as 350 Ma. Abstract : Coupled with strong evidence for frequent fire throughout the Permian‐Carboniferous and fossil evidence for other fire‐related traits, we conclude that many early conifers were serotinous in response to intense crown fires, indicating that fire may have had a major impact on the evolution of plant traits as far back as 350 Ma.